2008
DOI: 10.1111/j.1540-6229.2008.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Community Gardens on Neighboring Property Values

Abstract: Cities across the United States that have considerable vacant land are debating whether to foster community gardens on that land, while cities with land shortages are debating when to replace gardens with other uses. Meanwhile, many cities are looking for new ways to finance green spaces. Little empirical evidence about the neighborhood impacts of community gardens is available, however, to inform the debate or to help cities design financing schemes. This article estimates the impact of community gardens on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(152 citation statements)
references
References 17 publications
5
143
0
4
Order By: Relevance
“…In one study, the presence of shared gardens raised property values by as much as 9.4% within 5 years of establishment 55 . Tax revenues from these property increases were estimated at half a million dollars per garden over 20 years, making initial investments from government agencies for community garden and farm projects cost-effective 55 . However, rising property values can have negative impacts for the substantial part of the population that does not own real estate, since it can lead to higher rents for low-income residents, which can cause large-scale exclusion of long-time, poorer residents.…”
Section: Economic Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, the presence of shared gardens raised property values by as much as 9.4% within 5 years of establishment 55 . Tax revenues from these property increases were estimated at half a million dollars per garden over 20 years, making initial investments from government agencies for community garden and farm projects cost-effective 55 . However, rising property values can have negative impacts for the substantial part of the population that does not own real estate, since it can lead to higher rents for low-income residents, which can cause large-scale exclusion of long-time, poorer residents.…”
Section: Economic Impactsmentioning
confidence: 99%
“…A few studies correlated the presence of UA with increased home values and household income 55,56 . In one study, the presence of shared gardens raised property values by as much as 9.4% within 5 years of establishment 55 .…”
Section: Economic Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…If in fact the capacity for UA to persist is greater in more affluent areas, previous findings that indicate gardens increase nearby property values over time, especially properties in impoverished neighborhoods is problematic [26], suggesting that the establishment of UA on unused land makes neighborhoods more attractive and increases real estate prices, increasing potential for UA to act as a mechanism for de facto environmental gentrification, economically dispossessing residents of the spaces they created through hard work and social organizing. These radical acts of reclaiming space for food sovereignty may inadvertently contribute to and perpetuate existing inequalities [11,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed associations between community gardening and health [1][2][3][4][5][6][7][8], social [6,9], and economic benefits [6,7,10], and gardening in general has been associated with cardiovascular [11,12] and mental [13][14][15] health benefits. Historically, backyard and community gardens have made substantial contributions to the food supply; World War II ''Victory Gardens'' have been credited with providing an estimated 40% of the U.S. vegetable supply [16].…”
Section: Introductionmentioning
confidence: 99%